Competition in the Financial Sector : Overview of Competition Policies - Claessens, Stijn (IMF Working Papers; Working Paper ;, 2009)
As in other sectors, competition in finance matters for allocative, productive and dynamic efficiency. Theory suggests, however, that unfettered competition is not first best given the special features of finance. I review these analytics and describe how to assess the degree of competition in markets for financial services. Existing research shows that the degree of competition greatly varies across markets, largely driven by barriers to entry and exit. I argue that changes in financial services industries require updated competition policies and institutional arrangements, but that practices still fall short. Furthermore, I show that developing countries face some specific competition challenges.